Viral Hepatitis in Dentistry – An overlooked contributor to disease burden and occupational hazard in India - Syed, Sabin; Keshan, Pranav; Rastogi, Aayushi; Kumar, Arpit; Varshney, Mohit; Bansal, Akanksha (Indian Journal of Community Health, 2021)
Introduction: Dental professionals are considered to be at high-risk for contacting blood-borne pathogen transmissions. Thus, making it necessary for dentists to be aware on prevention, transmission and management of viral hepatitis. Objective: One day training programs for upskilling dental fraternity were conducted on 11th November 2019 and 11thFebruary 2020. Program also evaluated the Knowledge, Attitude, and Practices (KAP) of dentists regarding infection control practices and oral manifestations of viral hepatitis. Methods: One-day training program viz. “Viral hepatitis in Dentistry” under project Programmed Approach to Knowledge And Sensitization on Hepatitis (PRAKASH) was organized and a cross-sectional study using 20-item-self-reported questionnaire was conducted among participating professionals from six states of India. Identifying information was removed during statistical analysis. Results: Total of 625 dental professionals were trained; of which 470 participated in the KAP study i.e. response rate was calculated to be 75% (470 out of 625). Females represented about 73.2% of the sample(n=470). Sample comprised of experts from all the branches of dentistry. Almost 97% of responders were from private dental institutes or clinics. Mean knowledge score was found to be 4.71 ± 2.04, however when compared with age, knowledge in older professionals > 25 years was higher at 5.00 + 2.10 than participants’ aged<25, 4.57 ± 2.00 (p value = 0.03). Participating professionals seems to be following precautionary practices regarding viral hepatitis in dental clinics in a comparable manner irrespective of their age i.e. mean practice score of 6.81 ± 1.82 in professionals’< 25 years of age and mean practice score 6.81 ± 1.67 in trainees > 25 years. Conclusion: Study raised concerns regarding poor knowledge about infection prevention control and management of viral hepatitis in dental settings. Limited interventions in terms of capacity building programs for dentists on viral hepatitis, highlight the necessity of continued education through such training programs.